2021
DOI: 10.3390/en14154577
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Functional Reliability of Two-Lane Highways

Abstract: Rural two-lane highways are the most common road type both in Poland and globally. In terms of kilometres, their length is by far greater than that of motorways and expressways. They are roads of one carriageway for each direction, which makes the overtaking of slower vehicles possible only when there is a gap in the stream of traffic moving from the opposite direction. Motorways and express roads are dual carriageways that are expected to support high speed travel mainly over long distances. Express roads hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…This drift can be categorized into three types when PTS is viewed through a statistical model with input data X and output processing data Y. The first type (or drift of the first kind) is the drift of input data X, which reflects changes in traffic flow density due to daily, weekly, or seasonal cycles [98] and other time-related factors. The second type (the drift of the second kind) is the drift of output data Y, which could manifest as a shift in the simulation model's trace graph relative to the PTS due to external factors.…”
Section: Impact Of Traffic Flow Dynamics On the Performance Of ML Modelsmentioning
confidence: 99%
“…This drift can be categorized into three types when PTS is viewed through a statistical model with input data X and output processing data Y. The first type (or drift of the first kind) is the drift of input data X, which reflects changes in traffic flow density due to daily, weekly, or seasonal cycles [98] and other time-related factors. The second type (the drift of the second kind) is the drift of output data Y, which could manifest as a shift in the simulation model's trace graph relative to the PTS due to external factors.…”
Section: Impact Of Traffic Flow Dynamics On the Performance Of ML Modelsmentioning
confidence: 99%
“…In the research, Rossi et al [8] evaluated endogenous traffic characteristics, which are thought to affect the speed distribution, flow rate, and flow composition. Ostrowski and Budzynski [9] demonstrated that the following road parameters have a substantial impact on travel time and flow speed on short and long road sections in Poland: variations in curvature, longitudinal slopes, as well as lane and shoulder width.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies referred to selected problems in the reconstruction of road accidents [5,22,28]. A separate group of papers analyzed selected aspects of road infrastructure and traffic control [3,6,23,24]. All of the data show that the weakest link in the road safety system is man, and more specifically, vehicle drivers.…”
Section: A Brief Overview Of the Content Of This Special Issuementioning
confidence: 99%